A Novel Strategy for Enhancing Performance of Rectangular Pulse Generators: Simulation and Optimization of Blumlein Pulse Forming Networks - Chuanwei Wang; Hongtao Li; Jinshui Xiao (IEEE Access)
This paper presents a novel strategy to enhance the performance of rectangular pulse generators by simulating and optimizing Blumlein pulse forming networks (PFNs). The proposed approach imitates the Blumlein transmission line structure and synthesis methods of an LC ladder network to set up Blumlein PFNs as a series of inductor and capacitor combinations, initially. Subsequently, an optimization design algorithm is utilized to derive the optimal device parameters. The effectiveness of this strategy is demonstrated through simulations, which reveal significant improvements in output pulse characteristics such as flat top, pulse width, and peak power. The optimized Blumlein PFNs exhibit better performance compared to traditional PFNs, making them a promising solution for boosting the functionality and efficiency of rectangular pulse generators. This research contributes to the development of advanced pulse generation techniques and can be applied across various fields, including high-power microwave, laser, radar, X-ray and high-voltage testing equipment.